2007
DOI: 10.1017/s0022215107006913
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in the head and neck: experience in India

Abstract: Objective: With improvement in economic and social conditions and the use of effective anti-tubercular therapy, the developed nations, and most developing nations, have enjoyed a decline in tuberculosis for several decades. It is now seen that extra-pulmonary presentations form a major proportion of new cases, especially since the advent of the acquired immunodeficiency syndrome epidemic. Therefore, it is important that otolaryngologists are aware of tuberculosis in the head and neck region and its varied mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
3
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 24 publications
4
62
3
9
Order By: Relevance
“…One patient had temporomandibular joint involvement, and one had TB of the nose. 7 In the present case the patient suffered from TB at the age of 19 years and underwent treatment for the same. The current medical status confirms the patient to be suffering from TB.…”
mentioning
confidence: 69%
“…One patient had temporomandibular joint involvement, and one had TB of the nose. 7 In the present case the patient suffered from TB at the age of 19 years and underwent treatment for the same. The current medical status confirms the patient to be suffering from TB.…”
mentioning
confidence: 69%
“…Tuberculosis of the parotid gland is a rare clinical entity even in countries where the disease is endemic [6,7]. Clinically, it generally presents as a localized, unilateral, slow-growing parotid mass with a certain degree of fixation indistinguishable from salivary gland tumors [8], in this cases the histopathological examination is characterized by tuberculoid granulomas, with caseous necrosis, Langhans giant cells and epithelioid cells.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al in the clinicopathological analysis of 180 cases with tubercular cervical adenitis emphasized that the usual presentation of cervicofacial lymphadenitis is with multiple lymph node involvement without the constitutional signs and symptoms of tuberculosis as in the case presented here [17]. Prasad et al performed a 10 year retrospective study on 165 Indian patients with head and neck tuberculosis and concluded that 75% of the patients did not have pulmonary involvement [18].…”
Section: Discussionmentioning
confidence: 86%